ANALISIS KUALITAS PELAYANAN PENGUJIAN KENDARAAN BERMOTOR DI KABUPATEN TEGAL (DI LIHAT DARI IKM) - Lailatul Istiqomah Dewi; Nina Widowati; Aloysius Rengga (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
The test vehicle is a vehicle assigned to address safety issues in the field of public transport safety concerns for users at both the regional and national level. This study aims to identify and menganilisis quality of services performed by the Department of Transportation, Communication and Information Tegal regency. Type used is descriptive qualitative, by using reference measurements on basis of the satisfaction indext KEP MENPAN No.63/7/2003 which consists of 14 elements